Transcriptional Reorganization of Drosophila Motor Neurons and Their Muscular Junctions toward a Neuroendocrine Phenotype by the bHLH Protein Dimmed - Luo, Jiangnan; Liu, Yiting; Nässel, Dick R. (Frontiers in Molecular Neuroscience, 2017)
Neuroendocrine cells store and secrete bulk amounts of neuropeptides, and display morphological and molecular characteristics distinct from neurons signaling with classical neurotransmitters. In Drosophila the transcription factor Dimmed (Dimm), is a prime organizer of neuroendocrine capacity in a majority of the peptidergic neurons. These neurons display large cell bodies and extensive axon terminations that commonly do not form regular synapses. We ask which molecular compartments of a neuron are affected by Dimm to generate these morphological features. Thus, we ectopically expressed Dimm in glutamatergic, Dimm-negative, motor neurons and analyzed their characteristics in the CNS and the neuromuscular junction. Ectopic Dimm results in motor neurons with enlarged cell bodies, diminished dendrites, larger axon terminations and boutons, as well as reduced expression of synaptic proteins both pre and postsynaptically. Furthermore, the neurons display diminished vesicular glutamate transporter, and signaling components known to sustain interactions between the developing axon termination and muscle, such as wingless and frizzled are down regulated. Ectopic co-expression of Dimm and the insulin receptor augments most of the above effects on the motor neurons. In summary, ectopic Dimm expression alters the glutamatergic motor neuron phenotype towards a neuroendocrine one, both pre- and postsynaptically. Thus, Dimm is a key organizer of both secretory capacity and morphological features characteristic of neuroendocrine cells, and this transcription factor affects also postsynaptic proteins.